Can palm oil be substituted? A rheological study of fat mixtures - Kovács, Anikó; Homolya, Szabolcs; Temesi, Ágoston; Unger-Plasek, Brigitta; Kaszab, Tímea; Badak-Kerti, Katalin (Frontiers in Nutrition, 2024)
Due to its distinctive fatty acid makeup, which makes it simple to utilise in various applications, palm oil is one of the most widely used fats in the food business. However, the increased palm oil production is causing global environmental issues, including the loss of rainforests. As a result, companies that use palm oil, particularly the food industry, must hunt for alternate sources of fat that can replace palm oil. Oleogels, which are created from liquid oils, are one of the potential substitutes. Another alternative is to combine solid fat and liquid oil, however, research in this area is scarce. To fill this gap, we used a fully hydrogenized rapeseed oil and sunflower oil mixture in three different ratios for our research. We examined the rheological behaviour of the mixtures using oscillatory and rotational viscometry. According to our results, 35% FH rapeseed oil sample yielded results most closely resembling the control palm mid fraction. Our findings show that replacing palm oil with a combination of completely hydrogenated rapeseed oil and sunflower oil is only viable to a limited degree from a rheological point of view.